Detection of circulating tumor cells is achieved by flow cytometry in melanoma patients - Fourdrain, Ludivine; Brochet, Théo; Clichet, Valentin; Chaby, Guillaume; Gubler, Brigitte; Garçon, Loïc; Arnault, Jean‐Philippe; Boyer, Thomas (Cytometry. Part B, Clinical cytometry, 2025)
Melanoma is an aggressive skin tumor whose incidence is rising sharply, and for which the determination of new prognostic factors is a major challenge. In oncology, circulating tumor cells (CTCs) are at the heart of much research, as they represent a source of tumor material obtained non‐invasively by liquid biopsy. With this in mind, this prospective, longitudinal study looked at the detection of CTCs in melanoma patients using the flow cytometry technique, and constitutes a proof‐of‐principle study, as molecular biology is the most widely used technique today to detect CTCs. The labeling strategy showed high sensitivity and specificity for melanoma cells. All 35 patients in the cohort presented at least one CTC at inclusion, demonstrating that the cells circulate regardless of the stage of the disease. However, a significant increase in the number of CTCs was observed in metastatic stages compared with non‐metastatic stages. With regard to the main prognostic factors for melanoma, no significant association was found between the number of CTCs and Breslow thickness or the presence of ulceration. This study must be continued in order to increase the size of the sample, with a more consistent longitudinal follow‐up, in order to gain a better understanding of the prognostic significance of CTCs.